Undercover Reporting The Truth About Deception - Kroeger, Brooke (Medill School of Journalism Visions of the American Press, 2012)
In her provocative book, Brooke Kroeger argues for a reconsideration of the place of oft-maligned journalistic practices. While it may seem paradoxical, much of the valuable journalism in the past century and a half has emerged from undercover investigations that employed subterfuge or deception to expose wrong. Kroeger asserts that undercover work is not a separate world, but rather it embodies a central discipline of good reporting-the ability to extract significant information or to create indelible, real-time descriptions of hard-to-penetrate institutions or social situations that deserve the public's attention. Together with a companion website that gathers some of the best investigative work of the past century, Undercover Reporting serves as a rallying call for an endangered aspect of the journalistic endeavor.